Global prevalence of compound heatwaves from 1980 to 2022 - Kun Zhang; Jin-Bao Li; Michael Kwok-Po Ng; Zheng-Fei Guo; Amos P.K. Tai; Shu-Wen Liu; Xiao-Rong Wang; Jie Zhang; Jin Wu (Advances in Climate Change Research)
Global warming has led to increasing occurrence of hot extremes, yet our understanding of the compound heatwaves (CHW) of both day and night—the most threatening and harmful type—remains limited. Here we use the air temperature from ERA5-Land datasets to analyze key characteristics of global CHW from 1980 to 2022. Our results demonstrate a pronounced increase in global CHW, with an annual cumulative intensity rising by 3.32 °C per decade (p < 0.001), approximately four times greater than the increases observed in individual heatwave types of daytime (0.73 °C per decade, p < 0.001) and nighttime (0.78 °C per decade, p < 0.001), respectively. High latitudes in the Northern Hemisphere, particularly the Arctic regions, have experienced the highest increases in CHW (>10 °C per decade), especially since 2005. Moreover, interannual variations of CHW are closely linked to major climate modes, displaying strong region-specific connections and varied lagged effect, particularly with ENSO and PDO in tropical regions. Altogether, these results reveal the unexpected prevalence of CHW in recent decades, emphasizing the urgent need to address its potential adverse impacts on human and ecosystem well-being.